Intestinal Parasitic Infections and their Relationship with Healthy Living Behavior and Nutritional Status in Children - Indra Elisabet Lalangpuling; Nurmila Sunati; Michael V.L. Tumbol; Kevin G. Pascoal; Jasman Jasman (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Intestinal parasitic infection is an infectious disease still found in tropical countries with inadequate implementation of Clean and Healthy Living Behavior (PHBS). Parasites that generally infect the intestines are soil-borne worms and protozoa. The worms that infect a lot are Soil Transmitted Helminths (STH), namely Ascaris lumbricoides, Trichuris trichiura, and Hookworm. Cryptosporidiosis is an infectious disease caused by infection with the protozoan Cryptosporidium sp. that causes watery diarrhea. Nutritional status is an important factor in the immune system. The purpose of this study was to identify STH and Cryptosporidium sp infections and link them with the application of PHBS and nutritional status in elementary school students in Wori District, North Minahasa Regency. This type of research is descriptive-analytic with a cross-sectional design. The sample amounted to 160 respondents from six elementary schools taken by purposive sampling. STH examination using the native method and Cryptosporidium sp examination using Zn modification staining, nutritional status measurement was carried out based on BMI / U. This study concluded that 100% of respondents were not infected with cryptosporidium sp parasites, 8% of respondents were infected with Soil-Transmitted Helminth and there was no relationship with nutritional status respondents where 87% of respondents have normal nutritional status, 5% undernourished, 6% well-nourished and 2% obese.